PENATAAN RUANG KAWASAN NAGARI DALAM RANGKA MENGOPTIMALKAN PARIWISATA DI NAGARI TIKU KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM - Eri Arianto; Yulfa Mulyeni; Yulia Nizwana; Aermadepa Aermadepa (LPPM Universitas Ekasakti Padang, 2023)
Regional development is one of the efforts to utilize all the potential of the area in supporting development activities. Regional potential is the basic capital for the development of a society in improving its welfare. The existence of the area's potential is a means of supporting various development activities, both in terms of infrastructure potential, natural potential, population potential and business potential of the population as well as the potential of integrated cultural areas that can be exploited and used to improve development results in the context of justice and equity in an area . An area that is developed and developing is greatly supported by the existence of regional potential. The regional area is the geographical condition of an area which provides various opportunities for an area to manage the potentials of the area within a region. Community business activities also include potential productive areas in contributing to development activities and their results. The existence of sources of livelihood and employment owned by a community in an area, will make a major contribution to development activities, especially in the economic sector which has the potential to increase the ability of an area to become self-sufficient. Based on the description above, it becomes a concrete reference that every spatial planning activity carried out by the Regional Government of West Sumatra, always refers to the whole life of the people, including their economy, to build a just and prosperous society, it is necessary to regulate the development of appropriate integrated cultural areas. with the regional spatial plan. The supporting and inhibiting factors that must be disseminated to the community so that the development of integrated areas according to the regional spatial layout plan can be applied properly, namely socializing the factors of understanding legal substance, institutional structure, local wisdom culture, community knowledge, facilities and infrastructure available to community members know and understand the application in setting regional spatial planning in a region of West Sumatra, which directly or indirectly contributes greatly in participating in developing regional spatial planning in their region.